Toxicity Test of Moringa (Moringa Oleifera Lam) Essential Oil with the Brine Shrimp Lethality Test (BSLT) Method - Ni Luh Putu Putri Setianingsih; I Wayan Sudiarta; A.A. Sagung Putri Risa Andriani; Gusti Ngurah Oka Jiwantara; Sang Ayu Made Agung Prasetiawati Djelantik; Kadek Dinda Rahayu Darmawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Moringa oleifera is an herbal plant that is found in the tropics and Indonesia. Bioactive compounds in clover are found in many parts of the leaves. The study aims to test the toxicity of the essential oils of moringa leaves against the larvae of Artemia salina Leach and to find out the composition of the essential compounds of the constituents of the oil of moringa leaves using the gas-mass spectrometer chromatography method. (GS-MS). The results of the study of the essential oil on the leaves of the Moringa Oleifera Lum were toxic to the larvae of the moringa leaves, Artemia salina Leach, with an LC50 value of 178.58 ppm. GC results on moringa leaves obtained fifteen (15) peak compounds. The potential of the leaves of moringa as an herbal plant that can be a pesticide, antibacterial, and anticancer